N-aryl groups are ubiquitous in cross-dehydrogenative couplings because they stabilize reactive intermediates - Tsang, Althea S.-K.; Hashmi, A. Stephen K.; Comba, Peter; Kerscher, Marion (Chemistry - a European journal, 2017)
The mechanism of cross-dehydrogenative coupling (CDC) reactions has been examined by experimental and computational methods. We provide a rationale for the ubiquity of the N-aryl group in these reactions. The aryl substituent stabilizes two intermediates and the high-energy transition state that connects them, which together represent the rate-determining step. This knowledge has enabled us to predict whether new CDC substrates will react either well or poorly.
Gesehen am 21.08.2017